Bandwidth Enhancement of Microstrip Antenna Using Dual Feed Line with Array 2x1 element for Radar Applications - Kuswanto, Hery; Alam, Syah; Surjati, Indra (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
Radar communication systems are needed to predict weather and other military needs. One of the important parameters required for a radar communication system is an antenna with high performance and broad bandwidth that can improve the resolution. The research proposes a single patch microstrip antenna that is rectangular and has a 8 GHz resonance frequency for radar applications that have high bandwidth and performance. The antenna was developed with two dual feed lines connected to the peradiation element with the 2x1 element array technique aimed at increasing the bandwidth of the frequency. The antenna is designed using a FR-4 substrate with a tangent loss of 0.0265, a dielectric constant ( |r) = 4.3, a substrat thickness (h) = 1.6 mm. The dimensions of the rectangular single patch microstrip antenna substrata are 20x20 mm2 and 35x35 mm2 for the dual feed line antenna design. Simulation results from the antenna development showed a 159.62% increase in bandwidth compared to the original antenna design. The reflection coefficient also increased from the original design antenna, which was -16.36 dB, to -25.64 dB or an increase of 56.72%. This antenna is very suitable and recommended to be applied as a receiver antenna on radar communications systems